The Effects of Exercise on Perceived Barriers and Benefits of Exercise by Cancer Survivors Post Treatment - Marshall, Timothy F.; Andzel, Walter; Spaccarotella, Kim (Journal of Basic & Applied Sciences, 2016)
Exercise may be used to attenuate cancer treatment-related side effects. However, the majority of cancer survivors do not participate in regular exercise. Purpose: This study examined changes in fitness parameters as well as perceived exercise benefits and barriers held by post-treatment adult cancer survivors, who participated in a 12-week structured exercise program. Methods: This study used a randomized controlled trial design. Participants were 24 post-treatment adult cancer survivors with various cancer diagnoses. The Exercise Benefits /Barriers Subscale (EBBS) questionnaire was used to evaluate perceived exercise benefits and barriers. Data was analyzed using a mixed-between-within ANOVA. Results: There were no significant differences in the total EBBS score (128.7 ± 23.2 v. 142.6 ± 17.8; p=.20) or the benefits (86.4 ± 17.2 v. 96.3 ± 12.9; p=.31) and barriers subscales (42.3 ± 7.8 v. 46.5 ± 6.1; p=.14). However, those in the exercise group were significantly more likely to respond that exercise participation would not cause fatigue (2.42 ±.90 v. 3.25 ± .45; p=0.04), but may decrease fatigue (3.0 ± .60 v. 3.17 ±.58; p=.03). Conclusion: Among cancer survivors, exercise participation may strengthen the perception that exercise reduces, rather than causes, fatigue.